Design and Implementation of State Grid Data Operation Management System Based on Stacking Integration Algorithm - Wang, Jiajia; Zhang, Bo; Yao, Wenjian; Pan, Yingnan; Cheng, Lin (2024 3rd International Conference for Innovation in Technology (INOCON), 2024)
When transmitting operation management information with State Grid data as the carrier, iterative matching between State Grid data and operation management is the essence of operation management, and the factors affecting operation management are data structure, management mode, management effect, and interference of hardware and software. In this paper, a Stacking integration algorithm is proposed to optimize State Grid's data, management mode, and mapping structure, and the management level, security, and database rationality are verified. The accuracy of the optimization results is confirmed. The results show that the integrated Stacking algorithm has more than 90% accuracy in management level, security, and data structure calculation, and the operation and management time is less than 6min, which is significantly better than the previous management systems and meets the requirements of State Grid data operation and management.